Hope and tradition: Jewish Renewal strategies to reconstruct Jewish theology - Posen, M-Josee (University of Ottawa (Canada), 2007)
Existing scholarly work on the contemporary Jewish Renewal movement focuses largely on its feminist assertions and the general practices and characteristics of adherents. This investigation examines the underlying theology expressed through the written work and authoritative texts of the movement's leadership, especially Rabbi Zalman Schachter-Shalomi. Using an interdisciplinary approach melded with the techniques of rhetorical criticism and qualitative research/grounded theory development, the study identifies and examines five strategies used by the Jewish Renewal movement to reconstruct Jewish theology. Those strategies are: reinterpretation of the fundamental themes of Jewish theology, God/Torah/and the people Israel, to suit contemporary sensibilities; deriving authority for that reinterpretation from both traditional and contemporary thinkers; emphasizing the imaginal to achieve redemption; expressing the interpretation in liturgy; and linking the interpretation to the greater purpose of providing a direction for post-Holocaust Judaism. This study demonstrates that Jewish Renewal reconstructs Jewish theology in a way that resonates with the postmodern ethos, yet is profoundly Jewish, being firmly rooted in Jewish sources and texts. While Renewal theology stands in tension with other contemporary Jewish theological trends, it nevertheless is making an important contribution to the development of a postmodern, post-Holocaust Judaism.
Keywords: Theology.; Education, Religious.